Symmetric and Asymmetric Multilevel Inverter Topologies With Reduced Device Count - Mohammed A. Al-Hitmi (14070780) (2023)
In this work, two new topologies of single-phase hybrid multilevel inverters for symmetrical and asymmetrical configurations are presented for use in drives and control of electrical machines and the connection of renewable energy sources. The proposed topology uses 2 dc sources, 12 switches, 1 flying capacitor, and 3 diodes to generate boosted 13-levels and 17-levels for symmetric and asymmetric configuration, respectively. Self-voltage balancing of its capacitor voltage regardless of load type, load dynamics, or modulation index is a key advantage of the suggested design. The higher performance of proposed topologies in terms of the total number of switches, TSV, THD, switch stress, and dc sources are demonstrated by comparing those with recently published topologies. In addition, a widely employed nearest level control modulation approach is used to provide output voltage levels with low THD. Finally, experiments were undertaken to validate the performance of the suggested topology. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2022.3229087